Effect of L-shaped slots on scour around a bridge abutment - Neveen Y. Saad (IWA Publishing, 2021)
Local scour is the most significant cause of bridge failure. Providing a short abutment with a straight slot has proved to be an effective method for reducing scour at this abutment. In this study, laboratory experiments have been conducted to investigate the effectiveness of using L-shaped slots in comparison to the commonly used straight slot, on the scour reduction at short vertical-wall abutment under clear-water flow conditions and uniform bed materials. The slots were just above the bed and their diameters equal to half the abutment's length. The results illustrated that it is essential to have a straight slot in any combination of slots, as any configuration without one is inefficient. Also, a combination of a straight slot with one side slot in the middle of the abutment's width gives better performance than an individual straight slot, as it reduces the depth, area, and volume of the scour hole by about 32.6, 26.8, and 43.6% respectively, in comparison to 23.2, 20.7, and 35.3% for the straight slot alone. Highlights Constructing a bridge across a river alternates the river flow pattern, and vortexes take place around the the abutments. These vortexes cause scour development.; Few researches have studied the behaviour of straight-slotted abutments.; The aim of the presented work is to investigate the behaviour of L-shaped abutment's slots in comparison to the commonly used straight slot.;